Long-term swallowing outcomes following type 1 laryngeal cleft injection. (January 2020) - Miller, Ashley L.; Caloway, Christen; Hersh, Cheryl J.; Hartnick, Christopher J.
Abstract: Introduction: Interarytenoid injection augmentation (IIA) during initial diagnostic endoscopy for aspiration and dysphagia has been described as both a diagnostic and therapeutic technique in the evaluation of type 1 laryngeal cleft (LC-1). IIA is additionally hypothesized to be a temporizing measure that facilitates improvement of swallowing function and potentially obviates the need for future formal endoscopic suture repair of LC-1. However, long-term (>6 month) outcomes of IIA for LC-1 remain largely unknown. The objective of this study was to evaluate the effect of IIA on long-term swallowing outcomes and need for formal endoscopic suture repair in patients with LC-1. Methods: This is a retrospective cohort study of patients age ≤24 months with pharyngeal phase dysphagia on preoperative videofluoroscopic swallow study (VFSS) who underwent IIA for LC-1 during diagnostic laryngoscopy and bronchoscopy at a single tertiary care academic subspecialty hospital from June 2017 to May 2018. Included patients underwent VFSS within 30 days of IIA and had documented SLP follow up at 6 months or more post-procedure. Exclusion criteria included prior cleft repair, gastrostomy tube dependence, additional procedures at the time of IIA, or lack of documented follow up. A total of 34 patients underwent LC-1 during study period with 24 included in final analyses. The primary outcome measure was improvement in safely swallowed consistency at 6 months or greater following injection. Secondary outcomes included need for formal suture LC-1 repair following IIA and comparison of 30-day and long-term swallowing function. Results: Median [range] age at injection was 15.3 [10.3–19.1] months and 50% were female (n = 12). Improvement was noted in 12 (50%) patients within 30 days of IIA, with 11 of 12 demonstrating sustained improvement at long-term follow up (10.3 [9.3–14.0] months). Among all patients, 15 of 24 (63%) demonstrated improvement compared to preoperative baseline. Six of 24 (25%) required formal suture repair of LC-1. Conclusions: IIA is a safe procedure that may result in both immediate and long-term improvement in dysphagia in select patients with LC-1. Additional studies are required to determine impact of IIA on pulmonary complications and hospital utilization and as well as patient- and caregiver-related outcome measures.